Toward determining melt pool quality metrics via coaxial monitoring in laser powder bed fusion. (January 2018) - Fisher, Brian A.; Lane, Brandon; Yeung, Ho; Beuth, Jack
Highlights: Beam power, beam velocity, and part temperature affect melt pool thermal emission. Melt pool thermal emission correlates strongly to melt pool cross sectional area. Simple sensors can be used to gain powerful insight in laser powder bed fusion. Abstract: The current industry trend in metal additive manufacturing is towards greater real time process monitoring capabilities during builds to ensure high quality parts. While the hardware implementations that allow for real time monitoring of the melt pool have advanced significantly, the knowledge required to correlate the generated data to useful metrics of interest are still lacking. This research presents promising results that aim to bridge this knowledge gap by determining a novel means to correlate easily obtainable sensor data (thermal emission) to key melt pool size metrics (e.g., melt pool cross sectional area).